Perbaikan Keselamatan dan Kesehatan Kerja dengan Metode HIRARC di PT. Sumber Rubberindo Jaya - Andreas Arif Gunawan; liem yenny bendatu (Jurnal Titra, 2015)
PT Sumber Rubberindo Jaya is a company that produces motorcycle tires. This company has implemented occupational safety and health but with limitation in providing personal protective equipment. Currently, some export customers require occupational safety and health as a condition of export. Therefore this research is to improve the occupational safety and health in the company. HIRARC method is used to analyze the safety and health of the company. The result shows 24% activities are categorized as low risk, 48% are categorized as moderate risk, 28% are categorized as high risk. There are 8 moderate risk activities from all areas and 9 high risk activities from raw materials, mixing, cutting, building drum, curing. Proposed improvements are given to fixing the floor, giving personal protective equipment (safety shoes, helmet) and safety sign, the path the forklift and various other things.